ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DITINJAU DARI GAYA KOGNITIF REFLEKTIF IMPULSIF - Minrohmatillah, Nilna (STKIP PGRI Tulungagung, 2018)
This research is aimed analyze how mathematical communication skills of students are reflective and impulsive cognitive style. This descriptive qualitative research is conducted using test method which has been adjusted to certain indicators. The subjects in this study were class students VII C in SMPN 1 Sumbergempol Tulungagung. The data analize with data reduction techniques, data presentation, and conclusion. The result shows that that students with reflective cognitive style are better at processing information and have mathematical communication skills better and superior to students with impulsive cognitive styles.Â Keywords: mathematics communication, reflective-impulsive